Needs Analysis to Develop of Project Based Learning Module Assisted by Heyzine Application to Improve Students’ Creative Thinking Skills - M Ilham; Dea Stivani Suherman; Ratnawulan Ratnawulan; Fadhila Ulfa Jhora (Jurnal Penelitian Pembelajaran Fisika, 2026)
Efforts to develop 21st century skills have been carried out by changing the curriculum from the 2013 curriculum to an independent curriculum based on 21st century learning. One of the main focuses in this ability is the development of four core competencies known as 4C, including critical thinking and problem solving skills, creativity and innovation, collaboration skills, and effective communication skills. One of the four most important skills that must be developed by students is creative thinking skills. However, in reality, mastery of this ability is still relatively low. This low ability is caused by the teaching materials used in the learning process that have not been fully designed to support students' creative thinking skills and the Project Based Learning (PJBL) learning model. This study aims to analyze the need for developing E-modules based on Project Based Learning (PJBL). This study uses a development research approach with a 4-D model (Define, Design, Development, and Disseminate), which is limited to the Development stage. The results of the study revealed three main findings from the needs analysis: (1) students' creative thinking skills are still low, with a score of 36; (2) Based on teacher interviews, the teaching materials used in the learning process have not been fully designed to support students' creative thinking skills, and the Project Based Learning (PJBL) learning model is one of the learning models applied by teachers but is not yet optimal; (3) Determination of student characteristics, with scores for each indicator, student background 70.25, student learning interest 67.5, student learning motivation 66.67, student learning style 70.88, and digital learning 76.38. The research conclusion obtained from the needs analysis is that the development of an E-Module based on the Project Based Learning model assisted by the Heyzine application to facilitate students' creative thinking skills is very much needed by students.